Examining Extinction in Evaluative Conditioning - Bandi, Sahil (Curtin University, 2025)
Evaluative conditioning involves the learning of attitudes and preferences. These attitudes and preferences can be unlearnt via extinction; however, recent research has shown that attitudes and preferences can relapse. The investigation examined whether presenting positive and negative stimuli alone during extinction would reduce relapse in evaluative conditioning. Across three experiment presenting additional stimuli did not reduce relapse.